2022
DOI: 10.3389/fmicb.2022.874709
|View full text |Cite
|
Sign up to set email alerts
|

1,4-Dihydropyridine as a Promising Scaffold for Novel Antimicrobials Against Helicobacter pylori

Abstract: The increasing occurrence of multidrug-resistant strains of the gastric carcinogenic bacterium Helicobacter pylori threatens the efficacy of current eradication therapies. In a previous work, we found that several 1,4-dihydropyridine (DHP)-based antihypertensive drugs exhibited strong bactericidal activities against H. pylori by targeting the essential response regulator HsrA. To further evaluate the potential of 1,4-DHP as a scaffold for novel antimicrobials against H. pylori, we determined the antibacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…As shown in Table 2, the anticipated products were obtained with a high yield and in a short reaction time (8-10 min). The structure of the prepared compounds was confirmed by Fourier transform infrared spectroscopy (FTIR), 1 H nuclear magnetic resonance (NMR), and 13 C NMR spectroscopy as well as high-resolution mass spectrometry (HRMS). Spectral data are described in the experimental section.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 2, the anticipated products were obtained with a high yield and in a short reaction time (8-10 min). The structure of the prepared compounds was confirmed by Fourier transform infrared spectroscopy (FTIR), 1 H nuclear magnetic resonance (NMR), and 13 C NMR spectroscopy as well as high-resolution mass spectrometry (HRMS). Spectral data are described in the experimental section.…”
Section: Chemistrymentioning
confidence: 99%
“…1,4‐DHPs includes drugs such as amlodipine [6], manidipine [7], and pranidipine [8] which are calcium channel blockers and are used to treat hypertension [9]. Some of the biological activities of 1,4‐DHPs include antiinflammatory [10], antituberculosis [11], antihypertensive [12], antimicrobial [13], cytotoxic [14], and AO [15] activities. Considering these important biological activities, many researchers have been encouraged to synthesize 1,4‐DHP and investigate their medicinal and medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…To date, some investigations have been carried out in order to validate HsrA and ArsR as effective therapeutic targets against H. pylori infection as well as discovering low-molecular weight inhibitors of these RRs exhibiting strong bactericidal activities against antibiotic-resistant strains of this pathogen ( González et al., 2019a ; González et al., 2019b ; González et al., 2020 ; Antoniciello et al., 2022 ; González et al., 2022 ). Notably, some of the novel antibacterial candidates evaluated in these studies, including natural flavonoids and 1,4-dihydropiridines, have shown in vitro antimicrobial activities in the range of those observed with first-line conventional antibiotics ( González et al., 2021 ; González et al., 2022 ).…”
Section: Tcrs As Targets For Novel Antimicrobials Against H...mentioning
confidence: 99%
“…To date, some investigations have been carried out in order to validate HsrA and ArsR as effective therapeutic targets against H. pylori infection as well as discovering low-molecular weight inhibitors of these RRs exhibiting strong bactericidal activities against antibiotic-resistant strains of this pathogen ( González et al., 2019a ; González et al., 2019b ; González et al., 2020 ; Antoniciello et al., 2022 ; González et al., 2022 ). Notably, some of the novel antibacterial candidates evaluated in these studies, including natural flavonoids and 1,4-dihydropiridines, have shown in vitro antimicrobial activities in the range of those observed with first-line conventional antibiotics ( González et al., 2021 ; González et al., 2022 ). In some cases, these novel antimicrobial candidates exhibited synergistic effects in combination with conventional antibiotics, leading to reversion of drug-resistant phenotypes ( González et al., 2019b ), but also showed minor antimicrobial actions on representative members of human normal microbiota ( González et al., 2022 ).…”
Section: Tcrs As Targets For Novel Antimicrobials Against H...mentioning
confidence: 99%
See 1 more Smart Citation